STATISTICAL ANALYSIS OF ENERGY CONSUMPTION DURING THE CUTTING OF FROZEN MEAT BLOCKS USING MULTIPLE EDGE TOOL - A. B. Lisitsyn; V. I. Ivashov; B. R. Kapovsky; O. E. Kozhevnikova (Теория и практика переработки мяса, 2016)
Abstract Currently, frozen meat blocks are widely used in meat processing for production of sausages and other meat products. Efficient grinding of frozen raw meat is an urgent task for meat industry professionals. The V.M.  Gorbatov All-Russian Meat Research Institute has developed energy- and resource-saving process for grinding of frozen meat blocks by milling. Determination of energy consumption for grinding of raw materials by multiple edge tools (milling tools) is the most important step in the creating of new type mincing machine.